Analisis Kualitas Butir-Butir Soal Ulangan Harian Pendidikan Agama Islam Dengan Menggunakan Iteman - Nurlaila; Martin Kustati; Rezki Amelia (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to analyze the question items based on the level of difficulty of the questions, the differentiating power of the questions and the function of distractors on the test questions for students at SMA Negeri 1 Rao Utara Class X. This research uses a quantitative descriptive approach, while the samples were taken from classes IPS 1 and X IPS 2 as many as 200 students. The results obtained from the analysis of 40 items using ITEMAN by analyzing the level of difficulty of each item obtained 15 items that were categorized at the difficult level, 15 items that were categorized at the medium level, and 10 items that were categorized at the easy level. So for this reason, the difficulty level of the questions needs to be lowered or re-evaluated. Furthermore, by analyzing the differentiating power of the test items, results were obtained with 7 questions in the very good category, 17 in the good category, 9 in the fair category and 7 in the poor category. Next, analyzing the function of the distractor, there were three questions that had to be replaced because they did not deceive the students in answering them.